Analisis Risiko Kesehatan Lingkungan Paparan PM10 Terhadap Pedagang Kaki Lima Di Jalan Raya Kebayoran Lama - Windy Oktaviani; Rony Darmawansyah Alnur (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Air pollution remains a challenging problem to overcome. Anthropogenic activities largely produce PM10 particles and are less than 10 µm in size. Street vendors on Jalan Raya Kebayoran Lama may be exposed to PM10 from their sales activities along the main road. This study aims to analyze the environmental health risks associated with PM10 exposure among street vendors on Jalan Raya Kebayoran Lama. This type of research is a descriptive quantitative study through the steps of Environmental Health Risk Analysis (ARKL). Air sampling was conducted at 3 locations at two measurement times, namely the afternoon and the evening, using the DustTrak Aerosol Monitor 8533. A total sampling technique was used, with 45 respondents. The data in this study were analyzed univariately and using ARKL. PM10 concentrations on Jalan Raya Kebayoran Lama at three sampling locations exceeded the Indonesian PM10 quality standard of 75 µg/m3, with an average PM10 concentration of 134 µg/m3 during daytime measurements and 230 µg/m3 in the evening. The RfC value used was 0.0087 mg/kg/day. The RQ calculation showed that 15 respondents had an RQ value >1, indicating an unsafe risk profile and requiring risk management to minimize exposure impact.